Honduras : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Honduras. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Honduras's request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries is discussed. The social consultation has allowed the government to implement a vital reform of public sector wage policy. A reduction in the pressure of the civil service wage bill is the key for restoring the sustainability of the public finances. An ambitious financial sector reform is designed to address bank fragilities; and far-reaching transparency and anti-corruption measures aim to improve governance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet